The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10517-016-3157-0
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Hyperoxic Component to Adaptation to Hypoxia Prevents Impairments Induced by Low Doses of Toxicants (Free Radical Oxidation and Proteins of HSP Family)

Abstract: We studied the possibility of preventing disturbances caused by administration of low doses of toxicants by adaptation to interval hypoxia and hyperoxia. The preventive protective effect of adaptation to hypoxia-hyperoxia manifested in suppression of free radical oxidation, decrease in the levels of HIF-1α and inducible HOx-1, and improvement of tolerance to physical exercises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“… 29 , 30 But animal research found that intermittent hypoxia-hyperoxia has greater protective preventive effect than intermittent hypoxia-normoxia does. 31 Further studies are warranted to better understand the biological consequences and possible risks in replacing normoxia with the hyperoxia in intermittent hypoxia conditioning.…”
Section: Protocols and Parameters Of Intermittent Hypoxiamentioning
confidence: 99%
“… 29 , 30 But animal research found that intermittent hypoxia-hyperoxia has greater protective preventive effect than intermittent hypoxia-normoxia does. 31 Further studies are warranted to better understand the biological consequences and possible risks in replacing normoxia with the hyperoxia in intermittent hypoxia conditioning.…”
Section: Protocols and Parameters Of Intermittent Hypoxiamentioning
confidence: 99%
“…Наблюдая пользу и положительное влияние адаптивных реакций в ответ на гипоксию, ученые исследовали различные https://doi.org/10.26442/20751753.2023.5.202272 режимы гипоксических тренировок. Наиболее перспективным представляется метод интервальных гипоксическихгипероксических тренировок (ИГГТ), где периоды нормоксии (дыхание атмосферным воздухом) заменяются дыханием гипероксичной смесью, содержащей 30-35% кислорода [45]. По мнению некоторых исследователей, последовательная смена гипоксических и гипероксических (вместо нормоксических) стимулов во время ИГГТ позволяет усилить сигнал, индуцированный АФК, без усиления гипоксии.…”
Section: модификация образа жизниunclassified
“…The total breathing time of GHM during one session is 10–15 min with a total session duration of 15–100 min ( Serebrovskaya and Xi, 2016 ). There are variants of IHT with alternating hypoxic and hyperoxic episodes (hypoxia-hyperoxia) ( Sazontova et al, 2016 ; Hadanny and Efrati, 2020 ) or hypoxic and hypercapnic episodes (hypoxia-hypercapnia) ( Welch et al, 2022 ).…”
Section: Basic Technology Of Normobaric Intermittent Hypoxic Trainingmentioning
confidence: 99%